Problems of embodying the theatrical script in the cinematic film - Mghames, ايمن كاظم (Basrah Arts Journal, 2022)
Theater is one of the old rhetorical arts, and whether the performances are based on religious ritual, rituals, ritual ceremonies in an ancient human civilization , and they are called dramatic appearance, as most or most of the elements of the show are present and available, and these appearances have evolved and the epics were the poetic textual pillar that developed it to a theatrical text presented in religious ceremonies,. They are distributed in the theater, tragedy, comedy, satyr, the three types have their audience and fans within the Athenian, so the three texts were the basic premise in the theatrical show and embodying completely without change , and the other elements of the theatrical performance change according to the events introduced by the show, including lighting, fashion and decor And communication with the recipient audience directly, without barriers except from the imaginary fourth wall that separates them, on the other hand, we note that cinema is one of the arts that communicating with recipients indirectly, and physical communication did not prevents spiritual and emotional communication between the recipients and what is shown on white cloths .It is a magical world that harmonizes the mind, mind, and emotions of the recipients, who watch a show composed of events and artistic time in a place that is constantly changing, and this creates a problem In the possibility of the theatrical film in the compatibility between the story of the theatrical text and the tremendous possibilities of cinema in the transformations of time, place and the period of theatrical event cinema, and the researchers question in the whole of the research was (Has the cinema been able to transfer the theatrical text to the cinematic preserving the spirit of the theatrical text)the researcher had presented the study according to the tagged title (problems of embodying the theatrical text in a movie / selected models). This study has four chapters: The first chapter: It includes the research problem, the importance of the research, the objective of the research, the limits of the research, and the definition of terms. The second chapter included two topics: The first topic: (The pillars and basic elements of the theatrical text). The second topic: (the basic elements of the cinematic film) As for the third chapter the researcher dealt with research procedures which include the research community ,the research tool and the research method., The fourth chapter included the results of research, consultations, proposals, a list of sources and references, as well as an abstract in English